X-ray absorption spectroscopy and density functional analysis of the Fe3+distribution profile on Al sites in a chrysoberyl crystal, BeAl2O4:Fe3+ - Kanokwan Kanchiang (2018)
© 2016 International Union of Crystallography. Chrysoberyl is one of the most interesting minerals for laser applications, widely used for medical purposes, as it exhibits higher laser performance than other materials. Although its utilization has been vastly expanded, the location of transition metal impurities, especially the iron that is responsible for chrysoberyl's special optical properties, is not completely understood. The full understanding and control of these optical properties necessitates knowledge of the precise location of the transition metals inside the structure. Therefore, synchrotron X-ray absorption spectroscopy (XAS), a local structural probe sensitive to the different local geometries, was employed in this work to determine the site occupation of the Fe3+cation in the chrysoberyl structure. An Fe K-edge X-ray absorption near-edge structure (XANES) simulation was performed in combination with density functional theory calculations of Fe3+cations located at different locations in the chrysoberyl structure. The simulated spectra were then qualitatively compared with the measured XANES features. The comparison indicates that Fe3+is substituted on the two different Al2+octahedral sites with the proportion 60% on the inversion site and 40% on the reflection site. The accurate site distribution of Fe3+obtained from this work provides useful information on the doping process for improving the efficiency of chrysoberyl as a solid-state laser material.